ITEM ANALYSIS USING RASCH MODEL ON GEOMETRY FOR GRADE 1 - Alim, Jesi Alexander; Hermita, Neni; Safitri, Nila; Wijaya, Tommy Tanu; Putra, Zetra Hainul; Pereira, Jerito; Alim, Melvi Lesma (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2021)
The purpose of this research is to analyse the problem associated with the geometry instructional materials for grade 1 students using the Rasch model. This is a descriptive research with a quantitative approach used to obtain information on the Wright map, item measure, and fit for instructors. Data were obtained by distributing a questionnaire containing 10 questions to 30 first-grade students in 192 Public Elementary Schools in Pekanbaru through Google form. The data collected were analysed using the Rasch model assisted by the Winstep or ministep version 3.73 application. The result showed that items 2 and 3 contained very difficult and easy questions, with a 0.30 indicating difficulty level. In conclusion, the test items used are valid and generally not difficult for students